Psychosocial and bioethical challenges and developments for the future of vascularized composite allotransplantation: A scoping review and viewpoint of recent developments and clinical experiences in the field of vascularized composite allotransplantation - Kumnig, Martin; Jowsey-Gregoire, Sheila G.; Gordon, Elisa J.; Werner-Felmayer, Gabriele (Frontiers in Psychology, 2022)
Vascularized Composite Allotransplantation (VCA) has evolved in recent years, encompassing hand, face, uterus, penile, and lower extremity transplantation. Accordingly, without central-ized oversight by USA OPTN or European Programs, centers have developed their own prac-tices and procedures that likely vary, and accordingly, present different levels of rigor to the evaluation process, internationally. The importance of psychosocial factors in the selection process and treatment course has been widely recognized, and therefore, several approaches have been developed to standardize and guide care of VCA candidates and recipients. We propose to develop an international multidisciplinary platform for the exchange of expertise that includes clinical, patient, and research perspectives. Patient perspectives would derive from peer education and the assessment of patient-reported outcomes. To establish a foundation for such a platform, future research should review and combine current VCA pro-tocols, to develop the framework for a standardized psychosocial evaluation and follow-up of VCA candidates and recipients.